Oferta De Alojamiento Y Turismo Accesible Del Cantón Guano, Provincia Del Chimborazo - Chicaiza Pacari, Inti Maldy (2024)
ABSTRACT: The project entitled " Lodging offer and accessible tourism in the Guano canton, province of Chimborazo." was carried out with the objective of analyzing the situation of lodging and its exclusion of certain tourism sectors, such as people with disabilities, who have faced discrimination due to the lack of accessibility in the system. To this end, research was carried out on lodging facilities in the Guano canton, including those registered in the tourism cadastre of the Ministry of Tourism, those registered in the municipality of Guano, as well as OTAs' lodging facilities. In addition, we collaborated with associations and educational institutions for people with disabilities to establish a correlation between the two variables. This study employed a mixed methodology, combining qualitative and quantitative approaches. Documentary research of previous theses was conducted to support the research, field work to collect information, explanatory analysis of each variable, and a correlational approach to measure the relationship between the variables. To test the hypotheses, the SPSS statistical program was used and the Cronbach's alpha test was applied, which allowed us to draw conclusions and propose improvements in accessibility for people with disabilities in the Guano canton's lodgings. It is crucial that accommodations have accessibility for people with disabilities, as this market has historically been excluded from tourism activities. Therefore, it is essential to initiate the implementation of accessible tourism and become a regional reference. Key words: Lodging, Accessible Tourism, Guano, Disability.